2019
DOI: 10.1108/arj-01-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the AICPA core competencies through the usage of the monopoly™ board game

Abstract: Purpose The purpose of this paper is to examine the learning outcomes of students enrolled in an introductory financial accounting course through their experience of playing the Monopoly™ board game and map those outcomes to a selected number of individual competency types addressed in the AICPA Core Competency Framework. Design/methodology/approach A longitudinal qualitative analysis was performed to analyze self-reported learning outcomes collected from undergraduate students enrolled in an introductory fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…Mobile learning has been widely used and has become a prominent study in educational research at home and abroad [ 35 ]. A summary of previous research points out that mobile learning is based on mobile products, learning with mobile network support, and other conditions [ 15 , 16 , 36 ]. Learning is not limited by time and space and can be continued anytime, anywhere.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile learning has been widely used and has become a prominent study in educational research at home and abroad [ 35 ]. A summary of previous research points out that mobile learning is based on mobile products, learning with mobile network support, and other conditions [ 15 , 16 , 36 ]. Learning is not limited by time and space and can be continued anytime, anywhere.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Game-based learning has flourished in recent years. Most research results directly support that game-based learning can improve learning motivation and effectiveness [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. However, the application of research in accounting education is still very lacking [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jurnal Penelitian dan Pendidikan IPS (JPPI) 17 (2): 93-100, 2023 http://ejournal.unikama.ac.id/index.php/JPPI belajar. Mousa (2019) Media monopoli memiliki kelebihan, diantaranya adalah memberikan pengalaman belajar yang menyenangkan dan dapat menjadikan siswa lebih berpartisipasi aktif dalam pembelajaran serta dapat membuat siswa aktif selama pembelajaran sehingga dapat membangun interaksi antara siswa. Dalam konteks ini, siswa diharapkan dapat menjawab pertanyaan-pertanyaan yang muncul pada bidak permainan monopoli, sehingga mereka dapat belajar sambil bermain.…”
Section: Pembahasanunclassified
“…Board games and simulation games are popular types of game-based learning. Mousa (2019) applied the Monopoly game in accounting classes and reported that students pick up soft skills such as problem solving, collaboration, communication, and critical thinking while playing the game. Tan et al (2021) modified the Monopoly game and demonstrated that the modified game produces higher-order thinking skills for students.…”
Section: Introductionmentioning
confidence: 99%